AFM observation of protein translocation mediated by one unit of SecYEG-SecA complex - Yui Kanaoka; Takaharu Mori; Wataru Nagaike; Seira Itaya; Yuto Nonaka; Hidetaka Kohga; Takamitsu Haruyama; Yasunori Sugano; Ryoji Miyazaki; Muneyoshi Ichikawa; Takayuki Uchihashi; Tomoya Tsukazaki (Nature Communications)
Abstract Protein translocation across cellular membranes is an essential and nano-scale dynamic process. In the bacterial cytoplasmic membrane, the core proteins in this process are a membrane protein complex, SecYEG, corresponding to the eukaryotic Sec61 complex, and a cytoplasmic protein, SecA ATPase. Despite more than three decades of extensive research on Sec proteins, from genetic experiments to cutting-edge single-molecule analyses, no study has visually demonstrated protein translocation. Here, we visualize the translocation, via one unit of a SecYEG-SecA-embedded nanodisc, of an unfolded substrate protein by high-speed atomic force microscopy (HS-AFM). Additionally, the uniform unidirectional distribution of nanodiscs on a mica substrate enables the HS-AFM image data analysis, revealing dynamic structural changes in the polypeptide-crosslinking domain of SecA between wide-open and closed states depending on nucleotides. The nanodisc-AFM approach will allow us to execute detailed analyses of Sec proteins as well as visualize nano-scale events of other membrane proteins.